2013
DOI: 10.14712/23361964.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk assessment for Neodryinus typhlocybae, biological control agent against Metcalfa pruinosa, for Austria

Abstract: The potential environmental risks of Neodryinus typhlocybae, a parasitic wasp from North America, were evaluated with regard to its safe use as an exotic biocontrol agent for the planthopper Metcalfa pruinosa in Austria. Following an earlier host range study of N. typhlocybae conducted in the laboratory, the present study assessed the potential for establishment and spread as well as negative indirect effects on non-target organisms. The potential release sites in Austria were analysed for matching of the clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Remarks -Neodryinus typhlocybae, originally a Nearctic species, has been introduced to several southern and Central European countries (Strauss 2012). However, it has not been intentionally introduced to Hungary, therefore its occurrence in Hungary remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Remarks -Neodryinus typhlocybae, originally a Nearctic species, has been introduced to several southern and Central European countries (Strauss 2012). However, it has not been intentionally introduced to Hungary, therefore its occurrence in Hungary remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…The first specimens of N. typhlocybae originating from the USA (area of Connecticut) were repeatedly released in northwestern Italy in 1987 and the following years (Girolami and Camporese 1994). Apart from many parts of Italy, N. typhlocybae was also introduced into Croatia, France, Greece, the Netherlands, Slovenia, Spain and Switzerland (Strauss 2009(Strauss , 2012. The appearance of the species in Austria, Hungary, Bulgaria and Slovakia during the last decade is associated with its natural dispersal across central Europe (Vétek et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Guillemaud, et al [57] reported two main factors promoting biological invasion: Human activities and the biological adaptation of species. Human activities, including international trade and movement of vehicles among local regions, are highly responsible for recent biological invasions by moving invasive species and causing long distance dispersal [4,5,9,14,25,27,[58][59][60][61][62]. Human activities also promote the dispersal of invasive species by modifying and disturbing natural habitats and providing the possibility of the introduction of new species into ecosystems [63].…”
Section: Invasion Route and Factors Promoting Dispersalsmentioning
confidence: 99%